Comparison of interactions of MgO‐based refractories with Li‐ion battery cathode materials during calcination. Issue 1 (29th July 2018) - Zhai, Pengtao; Chen, Liugang; Hu, Shuhe; Zhang, Xuan; Ding, Dafei; Li, Hongxia; Li, Suping; Zhu, Lingling; Ye, Guotian
Abstract: To select refractory major ingredients of saggers for the calcination of Li‐ion battery cathode Li(Nix Coy Mnz )O2 (LNCM) materials, interactions between MgO‐based refractories, ie, magnesium aluminate (MgAl2 O4 ) spinel, forsterite (2MgO·SiO2 ), and cordierite (2MgO·2Al2 O3 ·5SiO2 ), and LNCM materials were compared respectively via refractory‐LNCM precursor cylinder testing in lab‐scale. The phase composition and microstructure evolution of the calcined cylinders were characterized and resulted in comprehensive understanding and comparing of degradation of the MgO‐based refractories. The results reveal that cordierite is severely corroded, whereas magnesium‐aluminate spinel reacts little with LNCM materials. Refractories contain both SiO2 and Al2 O3 with a higher SiO2 level will suffer a more serious corrosion contacting with LNCM materials.